Taping to improve scapular dyskinesis, scapular upward rotation, and pectoralis minor length in overhead athletes - Ozer, S. T.; Karabay, D.; Yesilyaprak, S. S. (Journal of Athletic Training, 2018)
Context: Deviations in scapular motions and subsequent alterations in associated soft tissues are thought to contribute to overuse shoulder injuries in overhead athletes. Whereas rigid and Kinesio taping are recommended for preventing these injuries, high-level evidence from clinical trials is still needed.